Деякі онтогенетичні аспекти впливу фізичних факторів на показники життєздатності у Drosophila melanogaster - Грачова, М.А.; Чешко, Т.М.; Шкорбатов, Ю.Г. (Фактори експериментальної еволюції організмів, 2015)
Aim. The aim of this work was to study the effects of electromagnetic factors at preembryonic and embryonic stages on viability of aging parents’ progeny in Drosophila. The infl uence of microwave irradiation (MW, f = 36,64 GHz, surface power density at the level of the object — 120 ± 0,05 mW/cm2 ; 15 cm from antenna edge; exposure time — 30 s), magnetic fi eld (MF; 25mT; exposure time 5 min) and their combinations (MW+MF and MF+MW) on rate of development; fecundity, embryonic and pupal lethality in Drosophila melanogaster stock Canton-S was investigated. Methods. The methods of recording of quantitative traits (rate of development; fecundity, embryonic and pupal lethality) and variation statistics were used. Results. The exposure to physical factors at embryonic stages the increase of Drosophila rate development was shown. MW also induced increasing pupal lethality being applied at embryonic stages. The MW+MF and MF+MW exposure of young fl ies raised embryonic lethality in progeny of the oldest parents. Exposure of imagoes to MW only resulted in increasing of pupal lethality of progeny. Conclusions. Electromagnetic factors that have been studied in this work signifi cantly modify the viability of Drosophila. These effects depend on both developmental stage at which the irradiation was applied and on parental age. Keywords: electromagnetic irradiation, developmental stage, viability, Drosophila.